The Use of Electronic Mail in Biomedical Communication - Costello, Richard (American Medical Informatics Association, 2000)
Objectives: To determine whether there are statistically significant differences in the content of electronic mail (e-mail) and conventional mail sent to authors of papers published in medical journals. Design: Prospective study by postal questionnaire. Over two one-month periods, corresponding authors of papers published in medical journals were asked to record details of the correspondence prompted by their publications. Measurements: Conventional and e-mail correspondence received. Reprint requests. Content of correspondence. Quality of correspondence. Results: Eighty-two of 96 authors replied. Fifty received e-mail (mean, 5.7 ± 8.8 e-mails per author) and 72 received conventional mail (15.5 ± 32.8 letters per author) (p ≪ 0.05). Seventy percent of e-mails and only 53% of correspondence sent by conventional mail (p ≪ 0.05) referred to the content of the paper. Conclusions: Publication in general medical journals stimulates more conventional than electronic mail. However, the content of e-mail may be of greater scientific relevance. Electronic mail can be encouraged without fear of diminishing the quality of the communications received.